2019
DOI: 10.1145/3373400.3373409
|View full text |Cite
|
Sign up to set email alerts
|

Energy-aware scheduling of malleable fork-join tasks under a deadline constraint on heterogeneous multicores

Abstract: This paper proposes an energy-aware scheduling of malleable fork-join (MFJ) tasks on heterogeneous multicores. This work allows a task to be split into multiple sub-tasks for fork-join parallel execution. The number of the sub-tasks is determined simultaneously with scheduling. Our scheduling technique aims at the minimization of energy consumption under a deadline constraint. In addition, this paper proposes a technique for simultaneous scheduling and core-type optimization. The technique optimally decides ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Many of these applications are broadly used in scientific and engineering domains, and constitute the dominant application type in many parallel benchmark suites extensively used for performance evaluation on symmetric and asymmetric multicore systems 7,11,14‐19 . Some of our insights on effective OS‐runtime interaction techniques could be leveraged for other types of programs, such as the increasingly popular task‐based parallel applications, where runtime scheduling has also drawn special attention 10,20‐22 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of these applications are broadly used in scientific and engineering domains, and constitute the dominant application type in many parallel benchmark suites extensively used for performance evaluation on symmetric and asymmetric multicore systems 7,11,14‐19 . Some of our insights on effective OS‐runtime interaction techniques could be leveraged for other types of programs, such as the increasingly popular task‐based parallel applications, where runtime scheduling has also drawn special attention 10,20‐22 …”
Section: Introductionmentioning
confidence: 99%
“…7,11,[14][15][16][17][18][19] Some of our insights on effective OS-runtime interaction techniques could be leveraged for other types of programs, such as the increasingly popular task-based parallel applications, where runtime scheduling has also drawn special attention. 10,[20][21][22] Previous research has demonstrated that the runtime system and the OS scheduler can perform optimizations on AMPs by leveraging hardware features that are directly controlled by the OS kernel and exposed to user space, such as performance monitoring counters (PMCs) 4,12,23 or dynamic voltage and frequency scaling (DVFS). 24,25 Often, the support to conveniently access new scheduling-relevant hardware features from the system software may take time to be adopted in operating systems, 4 or it may come in the form of architecture-specific interfaces that limit application portability or make its utilization impossible from particular levels of the software stack.…”
mentioning
confidence: 99%
“…We should highlight that the OpenMP specification [36] also provides extensions for the creation of task-based parallel applications. Despite the fact that many legacy parallel programs do not exploit task parallelism, there already exists a large body of work that pursues the efficient execution of task-based parallel applications on asymmetric multicores [8,12,13,35,45].…”
Section: Introductionmentioning
confidence: 99%